2016
DOI: 10.1002/jemt.22640
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in antennal morphology and sensilla ultrastructure of a pupal endoparasitoidTetrastichus howardi(Olliff) (Hymenoptera: Eulophidae)

Abstract: Tetrastichus howardi (Olliff) (Hymenoptera: Eulophidae), a pupal parasitoid of a great number of Lepidoptera pests, has a great potential for biological control. To investigate the olfactory system of this parasitoid, we examined the morphology and ultrastructure of the antennal sensilla of both male and female T. howardi using scanning and transmission electron microscopic techniques. Antennae of male and female T. howardi were geniculate in shape, which consisted of scape, pedicel and flagellum with 5 and 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Previous research on many Hymenoptera belonging to different families also suggested that Böhm may function as proprioceptors perceiving antennal movement (Xin et al, 2010; Hong et al, 2016). SCa have also been found in many insects, including Coleoptera and Hymenoptera species (Zheng et al, 2016; Faucheux & Kundrata, 2017). In the SCa, the curve of the sensory dome is modified by the stretching and muscular contractions of the pedicel, and also by external pressure on the sensillum dome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research on many Hymenoptera belonging to different families also suggested that Böhm may function as proprioceptors perceiving antennal movement (Xin et al, 2010; Hong et al, 2016). SCa have also been found in many insects, including Coleoptera and Hymenoptera species (Zheng et al, 2016; Faucheux & Kundrata, 2017). In the SCa, the curve of the sensory dome is modified by the stretching and muscular contractions of the pedicel, and also by external pressure on the sensillum dome.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical cluster analysis was used to analyze similarities between 16 parasitoids of Eulophidae species based on the types of antennal sensilla, such as Tetrastichus hagenowii Ratzeburg (Barlin et al, 1981), Sympiesis sericeicornis Nees (Meyhofer et al, 1997), Aprostocetus fukutai Miwa & Sonar and Aprostocetus prolixus La Salle & Huang (Wang et al, 2007), Diglyphus isaea Walker (Zou et al, 2009), Microdonophagus levis Schauff and Microdonophagus woodleyi Schauff (Hansson, 2009), Tamarixia radiata Waterston (Onagbola et al, 2009), Tetrastichus brontispae Ferrière (Xin et al, 2010), Tetrastichus nigricoxae Yang (Wang et al, 2012), Chouioia cunea Yang (Xu et al, 2013), Tetrastichus planipennisi Yang (Gao et al, 2013), Tetrastichus howardi Olliff (Zheng et al, 2016), Tetrastichus septentrionalis Yang (Hong et al, 2016), and Trichospilus pupivorus Ferrière (Da Silva et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the antennae of the fourth-and fifth-instar nymphs, only one SCA was presented on the second segment of the antennae. The SCA seems to occur in aging nymphs (the fourth-instar nymph of A. dispersus and the fifth-instar nymph of P. pyricola) [27,32] or adults (Tetrastichus howardi and A. dispersus) [35,46]. Previous studies have reported that the SCA with no pores in their cuticular structure play the role of mechanoreceptors [29,37,[47][48][49][50][51], whereas the SCA with pores was involved in gustatory system as well as in humidity reception [52].…”
Section: Plos Onementioning
confidence: 99%